2012
DOI: 10.1177/1545968311429688
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of Between-Limb Synchronization of Standing Balance Control and Falls During Inpatient Stroke Rehabilitation

Abstract: Background-Stroke-related sensorimotor impairment potentially contributes to impaired balance. Balance measures that reveal underlying limb-specific control problems, such as a measure of the synchronization of both lower limbs to maintain standing balance, may be uniquely informative about poststroke balance control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 31 publications
(49 reference statements)
5
74
0
4
Order By: Relevance
“…It is also important to note that these two groups did not differ in age or motor impairment of the foot: two other factors that are related to standing balance. 7,28 Taken together the present results further support the role of plantar sensation in creating spatial distribution cues used by the postural control system to guide forces applied to the ground and weight transfer between the legs. 15,16 The present ROC analysis provides a cutoff for plantar sensation monofilament testing, 4.31 log(mg), that may be clinically useful in terms of guiding treatment for balance impairment post-stroke as defined by increased COP variability in the ML plane.…”
Section: Roc Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…It is also important to note that these two groups did not differ in age or motor impairment of the foot: two other factors that are related to standing balance. 7,28 Taken together the present results further support the role of plantar sensation in creating spatial distribution cues used by the postural control system to guide forces applied to the ground and weight transfer between the legs. 15,16 The present ROC analysis provides a cutoff for plantar sensation monofilament testing, 4.31 log(mg), that may be clinically useful in terms of guiding treatment for balance impairment post-stroke as defined by increased COP variability in the ML plane.…”
Section: Roc Analysissupporting
confidence: 80%
“…6 While the relationship of standing balance to motor impairments has been well investigated, the role of stroke-related sensory impairments has received less attention. [7][8][9] This is despite the fact that the prevalence of somatosensation deficits poststroke (which includes proprioception and cutaneous sensation) ranges from 33 to 65%. [10][11][12] These deficits are mainly caused by damage to the primary somatosensory cortex which results in the inability to perceive, process, and interpret sensory feedback.…”
Section: Introductionmentioning
confidence: 84%
“…Others have observed asymmetric contribution of each lower limb to quiet standing balance control post-stroke; specifically, the non-paretic limb appears to contribute more to balance control than the paretic limb [24]. Previous work has demonstrated lower between-limb synchronisation of COP among individuals with stroke compared with healthy controls [18], and found that this reduced synchronisation is related to increased falls experienced during inpatient rehabilitation [19]. The current work demonstrates that reduced contribution of the paretic limb to balance control and reduced between-limb synchronisation are related to increased risk of falls in the community.…”
Section: Discussionmentioning
confidence: 90%
“…The contribution of the paretic limb to balance control was calculated by dividing the RMS of antero-posterior COP under the more-affected limb by the sum of the RMS of antero-posterior COP under each limb [16,17]; a value of 0.5 indicates that both limbs contribute equally to balance control, <0.5 indicates that the less-affected limb contributes more to balance control, and >0.5 indicates that the more-affected limb contributes more to balance control. Between-limb synchronisation of antero-posterior COP was calculated by determining the correlation coefficient between the left and right antero-posterior COP [18,19]. Antero-posterior COP was used for the contribution and synchronisation measures as individual-limb medio-lateral COP is less meaningful for overall bipedal balance control [20].…”
Section: Quiet Standingmentioning
confidence: 99%
“…For example, PC during quiet standing has been routinely used for many years [25,20,33,34,36], with variations including: standing with bare feet [25]; with shoes on [8,4,29]; with eyes open or closed [25,24]; and with legs spaced a fixed distance and arms crossed on chest [17]. PC during quiet stance has also been evaluated over different trial durations ranging from 30 -120 seconds [33].…”
Section: Postural Control (Pc) During Quiet Standing Is An Important mentioning
confidence: 99%